?COMPARISION OF INFILTRATION MEASUREMENT TECHNIQUES IN BORDER IRRIGATION - Islamr, Md. Nazrul; Hassan, Ahmad Ali; Dey, Kajal Kumar (Biological Sciences - PJSIR, 1999)
Volume balance and cylinder infiltrometer method of infiltration measurements were carried out at Bangladesh Agricul- tural University farms to determine the infiltration characteristics in Border irrigation for better irrigation management. First, second and third irrigation trials were conducted in non-vegetative border and fourth trial was conducted in vegetative border (Maize crop). The rate of application of water in first, second, third and fourth trial were 12.42,2.21, 5.19 and 5.191 s’, respecti vely. A general equation of infiltration rate was developed for the study area and comparison was made between Volume balance method and Cylinder infiltrometer method. It was observed that for all the trials cumulative infiltration and infiltration rate by Volume balance method was higher than that of cumulative infiltration and infiltration rate by Cylinder infiltrometer method. It was also observed that the values of infiltration characteristic constants a and b by Volume balance method were higher than those of the values of a and b by Cylinder infiltrometer method.